Longitudinal Reciprocal Relationships Between Discrimination and Ethnic Affect or Depressive Symptoms Among Chinese American Adolescents. - Hou, Yang; Kim, Su; Wang, Yijie; Shen, Yishan; Orozco-Lapray, Diana (Journal of Youth & Adolescence, 2015)
Discrimination plays an important role in the development of ethnic minority adolescents. However, previous studies have often adopted a unidirectional model examining the influence of discrimination on adolescent development, thus leaving the potential reciprocal relationship between them understudied. Moreover, there is a dearth of studies on Chinese Americans in the discrimination literature. Therefore, this study aimed to examine the reciprocal relationships between discrimination and two measures of adolescent outcomes (i.e., ethnic affect and depressive symptoms) from early adolescence to emerging adulthood in Chinese Americans. Participants were 444 adolescents (54 % female), followed at four-year intervals, beginning at 7th or 8th grade ( M = 13.03) in 2002, for a total of three waves. An examination of cross-lagged autoregressive models revealed two major findings. First, in contrast to the rejection-identification model, perceived discrimination at early adolescence negatively related to ethnic affect at middle adolescence. Conversely, ethnic affect at early adolescence also negatively related to discrimination at middle adolescence. These results held the same direction but became insignificant from middle adolescence to emerging adulthood. Second, perceived discrimination positively related to depressive symptoms across the studied developmental periods, and depressive symptoms positively related to perceived discrimination from middle adolescence to emerging adulthood. The strength of these longitudinal relationships did not change significantly across developmental periods or gender. These findings highlight the bidirectional relationship between perceived discrimination and adolescent outcomes; they also demonstrate the value of studying the discrimination experiences of Chinese Americans.